Knowledge, Attitudes, Motivations, Expectations, and Systemic Factors Regarding Antimicrobial Use Amongst Community Members Seeking Care at the Primary Healthcare Level: A Scoping Review - Nishana Ramdas; Johanna C. Meyer; Natalie Schellack; Brian Godman; Eunice Turawa; Stephen M. Campbell (Antibiotics)
Background/Objectives: Antimicrobial resistance (AMR) is a major global health challenge, particularly in low- and middle-income countries (LMICs). Understanding the knowledge, attitudes, motivations, and expectations of community members regarding antimicrobial use is essential for effective stewardship interventions. This scoping review aimed to identify key themes relating to the critical areas regarding antimicrobial use among community members in primary healthcare (PHC), with a particular focus on LMICs. Methods: OVID Medline, PubMed, and CINAHL databases were searched using Boolean operators and Medical Subject Headings (MeSH) terms relevant to antimicrobial use and community behaviors. The Population, Intervention, Comparison, Outcome, and Study Design (PICOS) framework guided study selection, which focused on community members seeking care in PHC in LMICs. Data management and extraction were facilitated using the Covidence platform, with the Critical Appraisal Skills Programme (CASP) qualitative checklist applied for qualitative studies. A narrative synthesis identified and grouped key themes and sub-themes. Results: The search identified 497 sources, of which 59 met the inclusion criteria, with 75% of the studies conducted in outpatient primary care settings. Four key themes were identified: (1) the ’patient’ theme, highlighting beliefs, knowledge, and expectations, which was the most prominent (40.5%); (2) the ’provider’ theme, emphasizing challenges related to clinical decision-making, knowledge gaps, and adherence to guidelines; (3) the ’healthcare systems’ theme, highlighting resource limitations, lack of infrastructure, and policy constraints; and (4) the ‘intervention/uptake’ theme, emphasizing strategies to improve future antibiotic use and enhance access to and quality of healthcare. Conclusions: Stewardship programs in PHC settings in LMICs should be designed to be context-specific, community-engaged, and accessible to individuals with varying levels of understanding, involving the use of information and health literacy to effectively reduce AMR.